Applied mechanics, behavior of materials, and engineering systems : selected contributiosn to the 5th Algerian Congress of Mechanics, CAM2015, El-Oued, Algeria, october 25-29 /: selected contributiosn to the 5th Algerian Congress of Mechanics, CAM2015, El-Oued, Algeria, october 25-29. (2016) - Unknown
No abstract available